Ribosomal DNA Gene Based Molecular Characterization of Sclerotium rolfsii causing Collar Rot in Amorphophallus paeoniifolius (Elephant Foot Yam) - Vidyadharan, Pravi; Jeeva, M. L.; Archana, P. V. (JOURNAL OF ROOT CROPS, 2017)
Amorphophallus paeoniifolius, commonly known as elephant foot yam (EFY), is an aroid with high yield potential and culinary and medicinal properties. Collar rot disease caused by Sclerotium rolfsii is an economically important disease prevailing in all Amorphophallus growing areas. As an initial phase of the study, the morphological characters of the pathogen was studied on PDA medium. The isolates varied in their growth parameters viz. growth rate, sclerotia production, sclerotia color, sclerotial distribution pattern and sclerotial size. Although valuable, traditional methods of pathogen detection do possess limitations and these constraints could be overcome by culture-independent molecular approaches. The present study utilized PCR assay for molecular characterization of ten S. rolfsii isolates based on the rDNA genes ITS and LSU. PCR assay using universal primers for ITS and LSU yielded single amplicons of 700 bp and 650 bp respectively. Sequence analysis of the amplified products showed higher similarity (97-100 % similarity) to S. rolfsii sequences in the GenBank database whereas less similarity to other species belonging to the same genus, thereby revealing the identity of the fungal species. The study thus corroborated the significance of ITS and LSU regions in molecular characterization of the pathogen and also divulged the possibility of designing S. rolfsii specific primers based on rDNA.